أثر ريادة الأعمال في تحقيق التنمية المستدامة من وجهة نظر القيادات الإدارية بجهاز استثمار مياه النهر الصناعي بالمنطقة الوسطى (Economic studies journal, 2019)
The objective of this study is to provide theoretical and practical concepts on the reality of entrepreneurship and its role in achieving sustainable development in the Great Man Made River project, as well as to verify the extent to which the ability of the project to understand and realize the concept of entrepreneurship. The study community consists of the administrative leaders represented by the heads of departments and the directors of the offices and administrations in the project, where a sample of about (43) members were taken. The statistical methods were used using the SPSS system to extract the results of the study and to analyze the responses of the sample members. Means, standard deviations, frequencies and other statistical methods were used to achieve the required results. The study reached several results; one of the most important results of the study was that there was a significant effect of the initiative on achieving the sustainable development in the Great Man Made River project, as well as the existence of a significant statistical impact of creativity on achieving sustainable development in the project. The study also showed that the level of application of risk tolerance was moderate, and that the level of application of taking advantage of opportunities in Great Man Made River project was high. The most important recommendations of this study were that the management of the project should look for the new horizons in the surrounding environment, and belief that the ideas of risk are mostly usefu
Keywords: Entrepreneurship; Sustainable Development